2014
DOI: 10.1155/2014/236245
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Hemodialysis Schedule in Patients with Higher Residual Renal Function at the Start of Dialysis

Abstract: We present an observational study to evaluate a progressive schedule of dose of dialysis, starting with 2 HD/week, when the renal clearance of urea was equal to or greater than 2,5 mL/min/1,73 m2and the patient is in a stable clinical situation. From 2006 to 2011, 182 patients started hemodialysis in our center, of which 134 were included in the study. Residual renal function (RRF), Kt/V, eKru, nPCR, hemoglobin, weekly erythropoietin dose, and beta-2-microglobulin were determined at 6, 12, 18, 24, and 30 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
7
6
0
Order By: Relevance
“…9 A. Mathew et al reported that, no statistical disparity with all-cause mortality in subgroups of age , gender , ethnicity, central venous catheter use or diabetes condition in preset subgroup analyses of the matched cohort compared incremental HD to conventional HD. 7 We found marked increase in UOP in incremental group; compared to conventional group; during the serial measurements (p < 0.05), which came in agreement with Liu et al 9 , A. Mathew et al 7 , Lucas et al 8 ,A. T. Mathew et al 10 and Merino et al 11 Liu et alreported that those on incremental HD appeared to be female and thinner relative to those on traditional HD. The amount of urine in the incremental HD group was higher relative to the conventional HD group 9.…”
Section: By Using Roc-curve Analysis Incremental Dialysissupporting
confidence: 87%
See 2 more Smart Citations
“…9 A. Mathew et al reported that, no statistical disparity with all-cause mortality in subgroups of age , gender , ethnicity, central venous catheter use or diabetes condition in preset subgroup analyses of the matched cohort compared incremental HD to conventional HD. 7 We found marked increase in UOP in incremental group; compared to conventional group; during the serial measurements (p < 0.05), which came in agreement with Liu et al 9 , A. Mathew et al 7 , Lucas et al 8 ,A. T. Mathew et al 10 and Merino et al 11 Liu et alreported that those on incremental HD appeared to be female and thinner relative to those on traditional HD. The amount of urine in the incremental HD group was higher relative to the conventional HD group 9.…”
Section: By Using Roc-curve Analysis Incremental Dialysissupporting
confidence: 87%
“…Regarding Baseline data, we found that; the mean age of all patients was (45.95 ± 2.97) years, and the average UOP was (1124.3 ± 337.2) ml/day. Regarding gender of the patients, the majority (60%) of patients were males; while (40%) were females, with (65%) had DM, and (75%) had HTN, which came in agreement with A. Mathew et al 7 and Lucas et al 8 .…”
Section: By Using Roc-curve Analysis Incremental Dialysissupporting
confidence: 86%
See 1 more Smart Citation
“…Dialysis strategies that protect RKF may therefore be beneficial. Observational studies have suggested that patients commencing 2XHD may have a slower rate of decline of RKF [22][23][24]. Incremental dialysis, whereby dialysis dose is individualized according to the prevailing level of RKF [8], might protect against RKF loss by reducing dialysis intensity for patients who retain significant RKF.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of RRF is a strong predictor of mortality and there are compelling reasons to preserve RRF . Knowledge of RRF not only provides useful prognostic information to clinicians but there has also been a resurgent interest to incorporate RRF in the hemodialysis prescription as part of ‘incremental dialysis’ with suggestions that it may help to preserve RRF .…”
mentioning
confidence: 99%